TUNTUTAN PEMBELAJARAN ABAD 21 DAN PEMBELAJARAN AKTIF - Dede Anggrayeni Saputri; Ainiya Widdatul Rachmah; Imam Turmidzi (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The 21st-century civilization is characterized by massive digital transformation, demanding the repositioning of education as the primary instrument for Human Resource (HR) development. This article aims to analyze the dynamics of 21st-century education, employment challenges in Indonesia, and the strategic role of professional teachers in producing an outstanding generation. The method used is descriptive qualitative analysis with a contemporary literature review and secondary data from the Central Bureau of Statistics (BPS). The results indicate that despite rapid technological advancements, human intervention remains an irreplaceable determinant pillar. However, Indonesia still faces HR quality constraints, reflected in high unemployment rates. Therefore, a transformation of educational patterns is required to integrate The 4C Skills and strengthen teacher competencies validated through certification. Professional teachers who are adaptive to the times are the key to internalizing students' character and functional skills to face global competition.